On Sea Turtle‐associated Craspedostauros (Bacillariophyta), with Description of Three Novel Species. Issue 1 (23rd December 2020) - Majewska, Roksana; Ashworth, Matt P.; Bosak, Sunčica; Goosen, William E.; Nolte, Christopher; Filek, Klara; Van de Vijver, Bart; Taylor, Jonathan C.; Manning, Schonna R.; Nel, Ronel
Abstract : The current study focuses on four species from the primarily marine diatom genus Craspedostauros that were observed growing attached to numerous sea turtles and sea turtle‐associated barnacles from Croatia and South Africa. Three of the examined taxa, C. danayanus sp. nov., C. legouvelloanus sp. nov., and C. macewanii sp. nov., are described based on morphological and, whenever possible, molecular characteristics. The new taxa exhibit characters not previously observed in other members of the genus, such as the presence of more than two rows of cribrate areolae on the girdle bands, shallow perforated septa, and a complete reduction of the stauros. The fourth species, C. alatus, itself recently described from museum sea turtle specimens, is reported for the first time from loggerhead sea turtles rescued in Europe. A 3‐gene phylogenetic analysis including DNA sequence data for three sea turtle‐associated Craspedostauros species and other marine and epizoic diatom taxa indicated that Craspedostauros is monophyletic and sister to Achnanthes . This study, being based on a large number of samples and animal specimens analyzed and using different preservation and processing methods, provides new insights into the ecology and biogeography of the genus and sheds light on the level of intimacy and permanency in the host–epibiont interaction within the epizoic Craspedostauros species.